Decrease in Operational Efficiency and Its Impact on the Production Capacity of the Combined Power Plant in Zawia (Comprehensive Journal of Science, 2025)
The Zawiya Combined Cycle Power Plant is considered one of the most important power generation stations in Libya, as it includes gas and steam units that contribute to supplying the national electricity grid. This research aims to examine the factors influencing the decline in the plant’s operational efficiency, most notably fuel quality, ambient air temperature, compressor efficiency in gas units, in addition to the deterioration of some auxiliary equipment and systems. Based on the operational data of the gas unit (GT12) during the period from January to June 2023, the results showed that efficiency decreased to (27.6%) compared to the design efficiency of (35%), representing a difference of (7.4%). This decline was reflected in the reduction of production capacity from (165) to (127) MWh per unit, resulting in a daily deficit estimated at (912) MWh, which negatively affected the overall daily output of the plant.
Keywords: Operational efficiency – Production capacity – Zawia Combined Power Plant – Gas turbines – Energy loss – Maintenance